2018
DOI: 10.1103/physrevb.97.075434
|View full text |Cite
|
Sign up to set email alerts
|

Large spin relaxation anisotropy and valley-Zeeman spin-orbit coupling in WSe2 /graphene/ h -BN heterostructures

Abstract: Large spin-orbital proximity effects have been predicted in graphene interfaced with a transition metal dichalcogenide layer. Whereas clear evidence for an enhanced spin-orbit coupling has been found at large carrier densities, the type of spin-orbit coupling and its relaxation mechanism remained unknown. We show for the first time an increased spin-orbit coupling close to the charge neutrality point in graphene, where topological states are expected to appear. Single layer graphene encapsulated between the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
128
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 49 publications
8
128
1
Order By: Relevance
“…The measurements of a large anisotropy of the in-plane and out-ofplane spin-relaxation times 17,24 can be interpreted 28 as an indication that a valley-Zeeman type SOC is also in-duced and its magnitude is comparable to the Rashba type SOC. This is consistent with the data extracted from SdH oscillations 13 and a similar conclusion was also reached in a more recent WAL measurement 20 . These measurements usually employed either bulk or few-layer TMDC substrate.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…The measurements of a large anisotropy of the in-plane and out-ofplane spin-relaxation times 17,24 can be interpreted 28 as an indication that a valley-Zeeman type SOC is also in-duced and its magnitude is comparable to the Rashba type SOC. This is consistent with the data extracted from SdH oscillations 13 and a similar conclusion was also reached in a more recent WAL measurement 20 . These measurements usually employed either bulk or few-layer TMDC substrate.…”
Section: Introductionsupporting
confidence: 93%
“…These heterostructures can posses functionalities that the individual constituent layers may not have. In order to increase the SOC in graphene, one of the most actively pursued directions is to interface it with materials that have strong intrinsic SOC, such as transition metal dichalcogenides (TMDCs) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . TMDCs are expected to be good candidates for graphene spintronics for two reasons: i) it was shown that TMDC substrates do not degrade the mobility of graphene 23,26 , and ii) they host a strong intrinsic SOC of the order of 100 meV (10 meV) in their valence (conduction) band 27 and hence can potentially be suitable materials for proximity induced SOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This thrust has been fueled by the prospect of enhancing spin-orbital effects in graphene [7,8], while preserving the quintessential Dirac character of its 2D quasiparticles. The much sought after interface-induced SOC has been recently demonstrated in graphene/TMD bilayer heterostructures [9][10][11][12][13][14], where sharp weak antilocalization features in the magnetoconductance data [11][12][13][14] and dramatic reduction of spin lifetimes [15][16][17] hint at a massive enhancement of spinorbit interactions in the 2D carbon layer (up to 10 meV), consistent with the predictions of model calculations and first-principles studies [10,18,19].…”
Section: Introductionsupporting
confidence: 53%
“…With respect to graphene/TMDC heterostructures, this approach has proven to be highly successful: measurements of weak antilocalization (WAL) indicate enhanced SOC in the graphene layer [6][7][8][9][10][11][12]; spin switches have been realized based on spin absorption in the TMDC layer [13,14]; predictions of giant spin relaxation anisotropy [15], which may be useful for orientation-dependent spin filtering, have been subsequently confirmed by experiments [16,17]; and recent measurements have indicated sizable charge-tospin conversion in the graphene layer [18,19]. Giant spin lifetime anisotropy has also been predicted in graphene/TI heterostructures [20], and recent measurements of spin transport and WAL have suggested that TIs also induce strong SOC in graphene [21,22].…”
Section: Introductionmentioning
confidence: 99%